Amount of Poverty as Policy Basis: A Forecasting Using The Holt Method - Syaharuddin Syaharuddin; Ahmad Ahmad; Vera Mandailina; Dewi Pramita; Mahsup Mahsup; Abdillah Abdillah (Universitas Bumigora, 2020)
This research aims to predict the growth of the number of poor people in every district and city in NTB Province of Indonesia for the next 10 years by using Holt exponential smoothing method. This type of research is quantitative research with input data used over the last 19 years with a measure of the goodness of models namely MSE, MAD, and MAPE. Based on the optimization results obtained the smallest parameter at α of 0.9 and β of 0.1, an average value MSE of 278005053.7, MAD of 9992.28222, and MAPE of 8.9374 Optimization results also provide information that the increase in the growth of the average poor population of 70206.6604 Certainly this result can be used as a guideline by the government in determining steps and responding to rapid response strategies in dealing with this poverty problem.